AB0550 DIFFUSING CAPACITY OF THE LUNG FOR CARBON MONOXIDE (DLCO) VS FORCED VITAL CAPACITY (FVC): SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS TO EXAMINE THEIR ABILITY TO MEASURE CHANGE IN CLINICAL TRIALS IN SYSTEMIC SCLEROSIS (SSC). (2nd June 2020) - Bellando Randone, S.; Cappellini, E.; Nidiaci, L.; Lepri, G.; Lazzaroni, M. G.; Campochiaro, C.; Bagnato, G.; Sambataro, D.; Sambataro, G.; Matucci-Cerinic, M.; Furst, D.
Abstract : Background: Lung involvement remains the main cause of morbidity and mortality in SSc. In 1 year clinical trials to assess lung involvement, FVC is usually evaluated and changes while the DLCO usually remains unchanged. In longer term observational studies, the DLCO often changes more than the FVC. Objectives: To examine, through a systematic literature review(SLR) and meta-analysis, whether DLCO%pred or FVC%pred (both to be designated solely as DLCO and FVC henceforth), responds more in assessing SSC interstitial lung disease in first year and longer term follow-up(FU). Methods: PubMed, EMBASE and COCHRANE databases were searched for english language articles on SSc published between 1960 and 31st October 2018. Any study that made reference to FVC and DLCO evaluation in SSc and reported their changes over the years was included. Reviewers double extracted articles to obtain agreement on>95% of pre-defined critical outcomes:DLCO and FVC at baseline, 1 yr of FU and at the last assessment interstitial lung disease by HRCT of the lungs study design, duration of FU. Other variables included demographics. In all cases I^2 test for heterogeneity was used and a result from 75 to 100% was considered as high heterogeneity.A random effects meta-analysis was used. Differences in the degree of change in FVC and DLCO were tested with t-test without compensation for repeated analysis. Results: 1870 articles were screened for eligibility and 21 were selected for the SLR and meta-analysis The analysis used 21 studies to evaluate changes of FVC and DCLO at 1 yr of FU. Only 5 studies were eligible to evaluate changes during longer FU (24.7 months(SD=20.4)). Heterogeneity was high at baseline and FU, (at 1 yr and >1 yr), both for the 21 studies at 1 yr (FVC:I^2 99.74%, 99.78%; DLCO: I^2=99.91%99.92%) and the 5 studies at > 1 year (FVC:I^2 92.86%;DLCO:I^2=99.54%), diminishing the confidence in the results. Table 1 gives the results of the random effects meta-analysis both for 21 and for the 5 studies evaluated. Regarding changes over 1 yr in the 21 studies, change of mean FVC was 2.7 (78.8vs81.5) while change in mean DLCO was 3.07(SE 8.20) (59.7vs 63.4). Considering the 5 studies during long term follow up, change in mean FVC was 2.0(7.36)(81.1vs83.1), and change in mean DLCO was -0.96 (16.95)(55.6vs54.7). Comparing the 1 yr changes in the 21 studies, change in mean FVC was 2.7(5.2)and change in mean DLCO was 3.07(8.2); difference in changes was not statistically significant (p=0.5791). During long term FU (24.7 months), change in mean FVC was 2.0(7.36)and change in mean DLCO was -0.96 (16.95); difference in changes was not statistically different (p=0.4698). Conclusion: Our data are limited by great heterogeneity. Given this limitation, this SLR and meta-analysis indicates that there is no difference in the changes comparing FVC to DLCO at either 1 yr or during longer term follow-up. Corroboration of these results in prospective studies and in registries to make clear, comparable comparisons will be needed. Disclosure of Interests: Silvia Bellando Randone: None declared, Eleonora Cappellini: None declared, Letizia Nidiaci: None declared, Gemma Lepri: None declared, Maria Grazia Lazzaroni: None declared, Corrado Campochiaro Speakers bureau: Novartis, Pfizer, Roche, GSK, SOBI, Gianluca Bagnato: None declared, Domenico Sambataro: None declared, Gianluca Sambataro: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Bristol-Myers Squibb, Speakers bureau: Acetelion, Lilly, Boehringer Ingelheim, Daniel Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Consultant of: AbbVie, Actelion, Amgen, BMS, Cytori Therapeutics, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Speakers bureau: CMC Connect (McCann Health Company)